THE PROVISION OF WAGES TO LAUNDRY LABOURERS SEEN FROM THE CONCEPT OF IJARAH BIL 'AMAL CONTRACT - Soraya Devy; Nila Vonna Rahmi (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2019)
Wages represent the entitlements of labourers that are procured and represented monetarily by the employer as just and suitable compensation. Wage disbursement is regulated and executed in accordance with a labour contract or agreement. The concept of ijarah bil 'amal, which pertains to the utilisation of an individual's labour in exchange for compensation for completed work, encompasses remuneration. The practise in Gampong Ulee Lueng Aceh of compensating labourers for laundering and ironing garments A situation in which the employee is required to bathe at the employer's residence without spending the night in exchange for the agreed-upon wage constitutes a besar. Wage determination is subject to variation contingent upon the location of employment. Nonetheless, some employees are assigned additional work without receiving additional compensation while they are at work. The purpose of this study is to determine how Islamic law evaluates the wage practises of ironing and washing labourers in Gampong Ulee Lueng. The findings of an investigation concerning the remuneration of garment laundering and ironing labourers in Gampong Ulee Lueng indicate that the prevailing method of compensating these individuals does not align with the principle of ijarah bil 'amal. Certain employees engaged in the linen and pressing industry perceive the remuneration as inequitable. According to the initial agreement, employees who engage in laundry and ironing duties are obligated to do so solely for the agreed-upon wage. In the future, however, the employees receive additional work without receiving additional compensation or similar benefits. Despite the fact that wages in Islam are dictated by the principles of equity and justice, this entails that one must be remunerated commensurate with the effort expended for each task accomplished, regardless of its magnitude. It is necessary for the obligations performed in conjunction with the rights acquired to be equitable in nature, ensuring that no party experiences disadvantage or injustice.